Self-testing and self-management of oral anticoagulation therapy in children - Christensen, Thomas Decker; Larsen, Torben Bjerregaard; Hjortdal, Vibeke E. (Thrombosis and Haemostasis, 2011)
Children and adolescents on oral anticoagulation therapy (OAT) present special challenges in terms of rapid fluctuations in International Normalised Ratio (INR) values, interruption in daily life due to frequent hospital/doctor visits, and difficulties and pain in the performance of venepuncture. Optimised management of OAT improves the quality of treatment, potentially accomplished by new methods such as patient self-testing (PST) and patient self-management (PSM). A review was performed, identifying 11 trials with children and adolescents. All studies had different methodological problems, predominantly by being non-randomised trials. A total of 284 patients were included with a mean follow-up of 22 months, finding a time within therapeutic INR target range between 63% and 84%. The coagulometers used for estimating the INR values were found to have sufficient precision and accuracy for clinical use, but external quality control is probably advisable. It can be concluded that PST and PSM are at least as good treatment options as conventional management in highly selected children. Larger studies, preferably randomised, controlled trials using clinical endpoints, are obviously needed in order to elucidate whether these new regimens of treatment are superior to conventional management of oral anticoagulation therapy.
Keywords: Paediatric; self-testing; self-management; anticoagulation; point of care